P Peran Guru dalam Mengembangkan Kemampuan Membaca pada Peserta didik di Madrasah Ibtidaiyah Darul Da'wah Wal Irsyad (DDI) Ujuna Kota Palu - Nurleli; aniati; Andi Nurfaizah (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2024)
Beginning reading, the reader does not yet have actual reading skills, but is still in the learning stage to acquire reading skills or abilities. The fact was found that in class III students at Madrasah Ibtidaiyah Darul Da'wah Wal Irsyad (DDI) Ujuna, Palu City, there were several students who were still reading with a halt, couldn't put words together, and some couldn't read. This thesis is entitled "The Role of Teachers in Developing Beginning Reading Skills in Class III Students of Madrasah Ibtidaiyah Darul Da'wah Wal Irsyad (DDI) Ujuna, Palu City". This type of research is field research using a descriptive qualitative approach. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. Based on the results of this research, it shows that: 1) The role of the teacher in developing the beginning reading skills of class III students at Madrasah Ibtidaiyah Darul Da'wah Wal Irsyad is that the teacher makes plans, the teacher acts as an innovator and motivator. 2) Supporting factors for teachers to develop initial reading skills in class III of Madrasah Ibtidaiyah Darul Dakwah Wal Irsyad are teacher factors, learning time and family environment. Meanwhile, inhibiting factors are students' lack of interest in learning and inadequate school facilities.The implications of this research include the need for attention from madrasah managers to improve facilities and develop buildings as well as adding classrooms and auditoriums. This is expected to increase students' interests, talents and language knowledge in elementary schools.